The Effects of Private Placements Announcement on Shareholders' Wealth and Trading Volume - Mohd Noor, Normaziah (2007)
This study examines the reaction of the stock price and the volume of trade surrounding the announcements of private placements in Malaysia. The wealth effects of private placements announcements over different economic conditions are examined based on different use of proceeds from the placement exercise, and different use of premium and discount in offer prices. Apart from studying the wealth and trading volume effects, the research in this study is extended to identify factors, which explain the price behavior of private placement announcements. This study used the event study methodology to measure the price behavior of private placements and the multivariate analysis is used to determine the variables explaining pnce behavior. The market-adjusted return method is employed to derive abnormal returns of private placement announcements. The analysis is conducted on 46 announcements of private placements for the period 1994 to 2003. The wealth effects, as measured by cumulative average abnormal returns (CARs), surrounding private placement announcements showed a pattern which is consistent with the findings in developed markets (Hertzel and Smith, 1993 and Wruck, 1989). The findings show significant positive wealth effect before the announcement day. The CAR for the period prior to the announcement date, CARs(-10,-1), is significant at 3.05 percent and statistically significant at 5 percent level. A reasonable explanation for these positive returns is the occurrence of information leakage prior to the announcement day. However, the average abnormal return (AAR) on the announcement date, AAR (1=0), is found to be negative (-0.63 percent) and it is statistically significant at 10 percent level. This is contrary to the evidence shown in the US but is consistent with the evidence in the Singapore market (Chen et el., 2002). It is possible that the negative returns are due to either market over-reaction or profit taking transactions by speculators who had traded on superior information before the announcement day. The results show that the cumulative abnormal returns (CARs) associated with private placements differs significantly across economic conditions at the time of issuance. The price reaction of Malaysian firms to private placement is sensitive to economic conditions at the time of the private placements. Private placements typically result in significantly negative CARs during economic downturns and significant positive CARs during economic gfowth. In addition, significant negative announcement reaction was observed when private placement proceeds are allocated for new project investment compared to the positive reaction for proceeds allocated for debt repayment and working capital requirements. The average volume of trade increases significantly for the entire analysis period. Private placements spark a large increase in trading activity during economic growth (before announcement day), during economic downturn (after announcement day), and when there are discounts in offer price sample and when funds are used for debt repayment. In the multivariate analysis of cumulative abnormal return (CAR) for each company with the determinants, it is found that offer price premium, book to market value ratio, proceeds to repay the debt, and the company's size provide statistically significant explanations of the variation in CAR. However, this study finds that the relative size of issues of private placement cannot explain the variation in CAR. Overall, the findings support the information signaling hypotheses, the wealth transfer hypotheses, the price pressure hypotheses, the firm quality hypotheses, and the information asymmetry hypotheses. However, there is no evidence to support investment opportunities argument effect. Private equity placements in Malaysia exhibit a strong positive relationship between abnormal returns and the price premium at which the shares are placed. The relationship suggests that placement price provides important information regarding a firm's quality and value.